Fair companies, satisfied seafarers: The mediating role of stress on board - Sić, Leon; Galić, Marko; Slišković, Ana (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
The maritime profession is characterised by high demands and stressors, which, according to previous studies, may lead to low levels of job satisfaction, and consequently reflect on health and safety. The goal of this research is to investigate the role of emotional intelligence and justice in the organisational context in explaining job satisfaction, as well as the role of stress on board in mediating the relationship between the examined predictors and job satisfaction. This research included seafarers from the Republic of Croatia (N=177), and the online questionnaire consisted of the Emotional Intelligence Questionnaire, the Stress on Board Scale, the Justice in the Organisational Context and the Job Satisfaction Scale. Higher levels of emotional intelligence directly contribute to higher levels of job satisfaction, whereas higher levels of organisational justice directly contribute to higher levels of job satisfaction, but also indirectly through lower levels of stress on the job. This study’s findings not only add to our understanding of seafarers’ job satisfaction, but also have important practical implications for shipping companies.